An Evolutionary Analysis of Orphan Genes in Drosophila - Domazet-Loso, Tomislav (Cold Spring Harbor Laboratory Press, 2003)
Orphan genes are protein-coding regions that have no recognizable homolog in distantly related species. A substantial fraction of coding regions in any genome sequenced consists of orphan genes, but the evolutionary and functional significance of orphan genes is not understood. We present a reanalysis of the Drosophila melanogaster proteome that shows that there are still between 26% and 29% of all proteins without a significant match with noninsect sequences, and that these orphans are underrepresented in genetic screens. To analyze the characteristics of orphan genes in Drosophila, we used sequence comparisons between cDNAs retrieved from two Drosophila yakuba libraries and their corresponding D. melanogaster orthologs. We find that a cDNA library from adults yields twice as many orphan genes as such a library from embryos. The orphan genes evolve on average more than three times faster than nonorphan genes, although the width of the evolutionary rate distribution is similar for the two classes. In particular, some orphan genes show very low substitution rates that are comparable to otherwise highly conserved genes. We propose a model suggesting that orphans may be involved in the evolution of adaptive traits, and that slow-evolving orphan genes may be particularly interesting candidate genes for identifying lineage-specific adaptations.